High Involvement Management and its Role in Achieving Performance Excellence: an Analytical Study for the Opinions of a Sample of Workers in a Number of Media Institutions in Duhok Governorate - Abdul Hamid Abdul Hadi AL-Zakholi, Hoshang; Kareem Mahmood, Othman (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The objective of this study is to identify the role of high involvement management with its dimensions (empowerment, information sharing, development and training practices, rewards) in achieving performance excellence with its dimensions (performance and achievement, initiative and creativity, cooperation and job commitment, participation and responsibility, continuous learning) in the media institutions in Dohuk Governorate. The descriptive analytical method has been used as a research methodology, and after reviewing the research literature, concepts were written and models and hypotheses were designed based on the dimensions of high involvement management and performance excellence. Scales have been developed and a questionnaire has been designed to collect data, and (173) questionnaires were distributed among the working individuals as a sample of a population of (238) individuals according to the statistical equations in all the fourteen media institutions in Dohuk governorate, by using the random sampling method. Several methods were used such as judges and Alpha Cronbach to ensure validity and reliability, and structural equation modeling to test its hypotheses, and the results showed a positive correlation and regression between the variables. Based on the results of the research, a number of recommendations were presented related to the need for media institutions managers to focus on following the dimensions of high involvement management in order to achieve performance excellence by individuals working in the surveyed institutions.